Exploration and Practice of Moral Education Courses in Universities in Big Data Era - Jing Liu (Advances in Multimedia)
Since the moral education acts an important role in daily life, the construction of moral education curriculum will have important consequences on the final effect of moral education work through the management of curriculum objectives, curriculum structure, curriculum content, curriculum implementation, and curriculum evaluation. The development and application of big data bring new direction for the enhancement and progress. This work gives the definition of big data in the teaching of moral education in universities. Secondly, the application status of big data in moral education teaching in colleges is studied. According to the existing research, the popularization of big data technology has completely changed the teaching concept of moral education in colleges and universities. Based on the second part, abundant theoretical research has been achieved and successfully applied in the teaching of moral education. Finally, this paper designs targeted big data strategies and analyzes the differences of different big data technologies in the effects of moral education to improve the effects of moral education in modern colleges and universities. The research of this paper has both theoretical and practical significance.